2009
DOI: 10.1097/qad.0b013e32832ec4ae
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of appearance and disappearance of HIV-1 integrase mutations during and after withdrawal of raltegravir therapy

Abstract: Complete viral suppression was important in order to prevent resistance emerging. RAL-resistance mutations were detected in the presence of other antiviral treatments, and the reverse of these mutations following RAL cessation suggests that a fitness deficit was conferred by these mutants. The observation that following RAL interruption virus rebound was with previously existing reverse transcriptase/polymerase mutations in the absence of integrase mutations implies that it is pre-RAL-archived viruses that re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…While a range of different mutations have been associated with resistance to RAL (reviewed in reference 33), resistance generally evolves in a stepwise process via one of several potential pathways. The mutually exclusive primary resistance mutations N155H, Q148H/R/K, and, more rarely, Y143R/C/H provide some resistance to RAL (9,14,15,28). These primary mutations often are associated with secondary mutations specific to each primary mutation pathway, which increase RAL resistance and may restore fitness defects caused by primary mutations (15).…”
Section: Stimulated Cd4mentioning
confidence: 99%
“…While a range of different mutations have been associated with resistance to RAL (reviewed in reference 33), resistance generally evolves in a stepwise process via one of several potential pathways. The mutually exclusive primary resistance mutations N155H, Q148H/R/K, and, more rarely, Y143R/C/H provide some resistance to RAL (9,14,15,28). These primary mutations often are associated with secondary mutations specific to each primary mutation pathway, which increase RAL resistance and may restore fitness defects caused by primary mutations (15).…”
Section: Stimulated Cd4mentioning
confidence: 99%
“…39,41 In some early treatment failures, virus populations containing N155H alone were observed to switch to virus populations with Q148R or H. Additional studies have also documented the dynamics of RAL resistance and the evolution of N155N/H to Q148H or N155H to Y143R in subjects with incomplete viral suppression. 45 The observation of InSTI resistance evolution during virologic failure may suggest that remaining on a RAL regimen could mitigate future therapeutic options within the InSTI class. However, some studies have suggested RAL may have persistent immunologic and virologic benefi t even after the development of resistance.…”
Section: Clinical Observations: Virologic Failure and Resistancementioning
confidence: 99%
“…Resistance mutations common to both of these first-generation integrase inhibitors have been reported and can result in high levels of drug resistance (26). Mutations which engender crossresistance between RAL and EVG have been reported in clinical trials, cell culture studies, and biochemical assays (9,26). This has prompted the search for second-generation integrase inhibitors that might display novel patterns of resistance, allowing their use in patients who have failed therapy with RAL or EVG.…”
mentioning
confidence: 99%